Acoustic Communication in Animals From Insect Wingbeats to Human Music (Bioacoustics Series Vol.1) - Seki, Yoshimasa (Singapore : Springer Nature Singapore : Imprint: Springer, 2023)
This book is the first volume of the bioacoustics series published by the Society for Bioacoustics. This volume provides an overview of the advances and recent topics in acoustic communication in various animals. Most animals produce vibrations and sounds by moving their body parts, including vocal organs. These sounds can be research targets of bioacoustics studies. How animals use these sounds, especially in inter-individual relationships, is the focus of this volume, "Acoustic Communication in Animals". The authors' expertise varies from molecular biology, neurobiology to psychology, and human brain imaging. Their research subjects range from invertebrates to humans. Despite the variety of topics, chapters are developed under the consideration of ethology and evolution. Readers will recognize the profundity of the topics in each chapter. In addition, the view and understanding of natural sound sequences produced by animals can vary among different cultures. Research from Japan and regions that have been underrepresented in previous literature can offer new ideas and unique perspectives in the study of bioacoustics. Readers can grasp the progress of this research field in a broad range of species in one book. The book presents multi- and interdisciplinary topics and appeals to researchers and students in fields including psychology, physiology, zoology, ethology, and neurosciences.
Chapter 1. Using knowledge about human vocal behaviour to understand acoustic communication in animals and the evolution of language and music -- Chapter 2. Acoustic communication in fruit flies and mosquitoes -- Chapter 3. Multiple functions of ultrasonic courtship song in moths -- Chapter 4. Recent progress in studies on acoustic communication of crickets -- Chapter 5. Vocal imitation, a specialized brain function that facilitates cultural transmission in songbirds -- Chapter 6. Dancing in singing songbirds: Choreography in Java sparrows -- Chapter 7. Vocal communication in corvids: who emits, what information and benefits? -- Chapter 8. Affiliation, synchronization, and rhythm production by birds -- Chapter 9. Cockatiels: a research subject for studying capability for music production -- Chapter 10. Acoustic properties and biological significance of ultrasonic vocalizations in rodents: emotional expressions -- Chapter 11. Effects of acoustic interference on the echolocation behavior of bats -- Chapter 12. Diverse sound use and sensitivity in auditory communication by chimpanzees (Pan troglodytes) -- Chapter 13. The Interplay among the linguistic environment, language perception, and production in children's language-specific development -- Chapter 14. Sound processing in the auditory periphery: toward speech communication and music comprehension.
Keywords: Life sciences; Cognition in animals; Neurosciences; Psychology; Animal culture; Psychology, Comparative; Life Sciences; Animal Cognition; Neuroscience; Behavioral Sciences and Psychology; Animal Science; Comparative Psychology